PENINGKATAN KETRAMPILAN DI PANTI AKHLAQUL KARIMAH KOTA MALANG DENGAN PROSES PEMBUATAN PRODUK NATURAL VIBER KOMPOSIT SERAT BATANG PISANG KEPOK (Musa Paradisiaca) - purkuncoro, aladin eko (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Independent skills can be fostered through ongoing training periodically with a pattern of implementation that has been determined by the government based on the level of community needs. The specific purpose of this service is to improve the skills and innovation of the Akhlaqul Karimah orphanage children in Malang, by making several products made from composite fiber kepok banana stem (Musa Paradisiaca). Currently the development of science and technology continues to develop in all fields, such as the field of vehicle construction, building construction, industry, and also in the field of material engineering, especially composites. This development is inseparable from the increasing need and scarcity of materials available in nature. The use of materials for industry still relies heavily on non-renewable mining materials. Therefore we need replacement materials that can be renewed, and have mechanical properties that can compensate for the superiority of mining materials. Composite material is material that combines the properties of two or more materials to form a new material that has the superiority of the properties of each of these materials.